Design of a Fuzzy Logic process Controller for flow applications and implementation in series tanks Pilot Plant - Al-Qutami, T.A.H. (Institute of Electrical and Electronics Engineers Inc., 2015)
Flow control is essential in many industrial applications such as chemical reactors, heat exchangers and distillation columns. Most industrial processes exhibit nonlinearities and inherit dead time, which limit the performance of conventional PID controllers. This Project is about the design and implementation of Fuzzy Logic Controller (FLC) for flow control applications. The objective is to overcome problems inherited with conventional PID control scheme such as handling unpredictable disturbance, non-measurable noise as well as further improve the transient state and steady state response performance. The proposed control scheme is implemented in Flow Control and Calibration Pilot Plant. The design is done using Matlab/Simulink software package and is connected to the Pilot Plant through USB-type DAQ cards. Simulation and implementation results showed that the developed controller has less overshoot, good control performance, better disturbance handling ability, great robustness and is more flexible and intuitive to tune. It is expected that this advanced controller improves efficiency and productivity of industrial processes through proper handling of any disturbance or noise and increase the robustness of controller actions. Â© 2015 IEEE.